INCREASING AUTONOMOUS LEARNING THROUGH PEER ASSESSMENT TECHNIQUE - Annisa Puspasari; Nurul Hudayani (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Working collaboratively with peers is one of the aspects that define learner autonomy. Peer assessment is a growing solution for writers to get an improvement. It allows students to work socially since they will know strengths and weaknesses of learning. Regarding to previous related studies, peer assessment in writing encourages students to be active and take a part of their own writing progress with their peers. (Ashley Landry, 2014). Furthermore, peer assessment can contribute and trigger student’s autonomous learning. (Kulsirisawad, 2012). It is also viewed as another way of challenging students dependence on the teacher for feedback and guidance in their language learning to emphasize learner autonomy and cooperation to get students involved and learn as much from each other as they can from the teacher (Hamid Ashraf, 2015). In this research, the writer applied peer assessment in Writing I class by considering some beneficial effects over student’s writing proficiency within the autonomous learning context as the Writing I is the beginning writing course in English Department of UIN Ar-Raniry Banda Aceh. The aim of this research to investigate the process of autonomous learning situation through peer assessment in Writing I class and find out the outcome of peer assessment in Writing I class. It was conducted by using experimental research. The population of consisted of 4 classes, consist of 119 students fourth semester. The instrument of collecting data is writing test. Based on the data analysis, the writer found that the score of the experimental class students was higher than the control class students. The analysis of research result shows that peer assessment is an appropriate technique for university students to foster learner autonomy especially in EFL writing class.